Climate Security Webinar: Benefits of Climate Adaptation for Poverty Reduction and Gender Equality - Roy, Shalini; Gilligan, Daniel O.; Läderach, Peter R.D. (CGIAR, 2023)
Climate adaptation isn’t just about protecting the environment; it’s a key tool for building a more equitable world. This webinar delves into the following crucial topics: How climate adaptation investments can lift communities out of poverty The role of gender considerations in climate resilience and poverty alleviation Global experiences and success stories in integrating climate action with social protection and rural development. Register for the Climate Security webinar series here: https://on.cgiar.org/3LISoQ6